A new numerical method for variable order fractional functional differential equations. (June 2017) - Li, Xiuying; Li, Haixia; Wu, Boying
Abstract: In this letter, a high order numerical scheme is proposed for solving variable order fractional functional differential equations. Firstly, the problem is approximated by an integer order functional differential equation. The integer order differential equation is then solved by the reproducing kernel method. Numerical examples are given to demonstrate the theoretical analysis and verify the efficiency of the proposed method.